Airway inflammation in the elite athlete and type of sport. Issue 4 (21st August 2007) - Belda, J; Ricart, S; Casan, P; Giner, J; Bellido-Casado, J; Torrejon, M; Margarit, G; Drobnic, F
Abstract : Background: The prevalence of asthma and bronchial hyper-responsiveness is greater in elite athletes than in the general population, and its association with mild airway inflammation has recently been reported. Objective: To study the relationship between the type of sport practised at the highest levels of competition (on land or in water) and sputum induction cell counts in a group of healthy people and people with asthma. Material and methods: In total, 50 athletes were enrolled. Medical history, results of methacholine challenge tests and sputum induced by hypertonic saline were analysed Results: Full results were available for 43 athletes, who were classified by asthma diagnosis and type of sport (land or water sports). Nineteen were healthy (10 land and 9 water athletes) and 24 had asthma (13 land and 11 water athletes). Although the eosinophil counts of healthy people and people with asthma were significantly different (mean difference 3.1%, 95% CI 0.4 to 6.2, p = 0.008), analysis of variance showed no effect on eosinophil count for either diagnosis of asthma or type of sport. However, an effect was found for neutrophil counts (analysis of variance: F = 2.87, p = 0.04). There was also a significant correlation between neutrophil counts and both duration of training and bronchial hyper-responsiveness among athletes exposed to water (Spearman's rank correlations, 0.36 and 0.47, p = 0.04 and 0.04, respectively). Conclusions: Elite athletes who practice water sports have mild neutrophilic inflammation, whether or not asthma is present, related to the degree of bronchial hyper-reactivity and the duration of training in pool water.